Bifurcation analysis of a discrete SIS model with bilinear incidence depending on new infection - Hui Cao; Yicang Zhou; Zhien Ma (Mathematical Biosciences and Engineering)
A discrete SIS epidemic model with the bilinear incidence depending on the new infection is formulated and studied.The condition for the global stability of the disease free equilibrium is obtained.The existence of the endemic equilibrium and its stability are investigated.More attention is paid to the existence of the saddle-node bifurcation, the flip bifurcation, and the Hopf bifurcation.Sufficient conditions for those bifurcations have been obtained.Numerical simulations are conducted to demonstrate our theoretical results and the complexity of the model.